2014
DOI: 10.1007/s10964-014-0180-1
|View full text |Cite
|
Sign up to set email alerts
|

Body Talk: Siblings’ Use of Positive and Negative Body Self-Disclosure and Associations with Sibling Relationship Quality and Body-Esteem

Abstract: The sibling relationship has been deemed the quintessential "love-hate relationship." Sibling relationships have also been found to have both positive and negative impacts on the adjustment of youth. Unlike previous research, however, the present study examined the associations between siblings' positive and negative body-related disclosures with relationship quality and body-esteem. Additionally, ordinal position, individual sex, and sibling sex composition were tested as moderators. Participants included 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The intended outcome of the peer norms processing instruction set was for participants to consider the ways in which their peers may use thin-ideal media to evaluate others' appearance, including the appearance of the participant. However, in line with suggestions by Hillard et al (2016), the inclusion of items to engage participants in consideration of their peers' appearance comparison behaviors or desires to look like media images, which were used to set up the premise that peers use media to compare themselves and others, could have produced a feeling of cohesion, or bonding between participants and their perceptions of their peers (Bassett Greer et al 2015;Hillard et al 2016), which reduced negative outcomes for some participants.…”
Section: Discussionmentioning
confidence: 89%
“…The intended outcome of the peer norms processing instruction set was for participants to consider the ways in which their peers may use thin-ideal media to evaluate others' appearance, including the appearance of the participant. However, in line with suggestions by Hillard et al (2016), the inclusion of items to engage participants in consideration of their peers' appearance comparison behaviors or desires to look like media images, which were used to set up the premise that peers use media to compare themselves and others, could have produced a feeling of cohesion, or bonding between participants and their perceptions of their peers (Bassett Greer et al 2015;Hillard et al 2016), which reduced negative outcomes for some participants.…”
Section: Discussionmentioning
confidence: 89%
“…For example, when adolescents disclosed information about body‐related issues—regardless of whether it was positive or negative—they had greater body esteem. Adolescents who were on the receiving end of these disclosures, especially younger sisters, had lower body esteem (Greer, Campione‐Barr, & Lindell, ). While issues related to body image are particularly salient to adolescents, so are issues surrounding dating and sexuality.…”
Section: Support and Positivity: Not All Goodmentioning
confidence: 99%
“…Additionally, studies have shown that negative weight-based talk by family members is associated with child and adolescent body dissatisfaction, unhealthy weight control behaviors, and depression (Eisenberg, Berge, Fulkerson, & Neumark-Sztainer, 2012; Greer, Campione-Barr, & Lindell, 2015; Keery et al, 2005; MacDonald et al, 2015), regardless of whether the child is overweight or normal weight.…”
mentioning
confidence: 99%
“…Most studies that have investigated negative weight-based talk focus on peer or family teasing. A few studies have included both parent and sibling variables (Greer et al, 2015; Schaefer & Salafia, 2014; Taylor et al, 2006), but to the best of our knowledge, only one study has examined family, parents, and siblings separately (Keery et al, 2005). In addition, the limited studies that have included siblings have been conducted mostly with Caucasian, mid- to higher-income participants.…”
mentioning
confidence: 99%